Revealing novel cytb and nad5 genes-based population diversity and benzimidazole resistance in Echinococcus granulosus of bovine origin - Alvi, Mughees Aizaz; Alshammari, Ayed; Ali, Rana Muhammad Athar; Ul Haq, Shahbaz; Bashir, Rizwan; Li, Li; Saqib, Muhammad; Sajid, Muhammad Sohail; Ghafoor, Muzafar; Imran, Muhammad; Ijaz, Muhammad Umar; Fu, Bao-Quan; et al. (Frontiers in Veterinary Science, 2023)
Cystic echinococcosis (CE) is a neglected zoonotic cestodal disease caused by Echinococcus granulosus. Parasite affects a wide range of livestock and wild animals. In this study, population diversity of Echinococcus species was investigated based on mitochondrial cytochrome b (cytb) and NADH dehydrogenase subunit 5 (nad5) genes. In addition to this, β-tubulin gene isoforms of Echinococcus granulosus were amplified to determine the resistance against benzimidazoles. For this purpose, 40 cyst samples from cattle (n=20) and buffaloes (n=20) were collected from the main abattoir of Sialkot. DNA extraction was performed using Qiagen Blood and Tissue kit. Amplification was performed through PCR. Each amplicon was confirmed by GelRedTM stained agarose gel (2%). Samples were sequenced in DNA analyzer and viewed for any misread nucleotide by using MEGA (v.11) Corrections in nucleotide sequence and multiple sequence alignment was made through the same software. NCBI-BLAST was used for sample specific sequence to identify it as belonging to a particular species. Diversity indices were estimated using DnaSP (v.6) while phylogenetic analysis was inferred using Bayesian method using MrBayes (v.1.1). β-tubulin gene isoforms sequence analysis was performed to find out candidate gene causing benzimidazole resistance. All the 40 isolates were found positive for E. granulosus. BLAST based searches of sequences of each isolate for each gene (nad5 and cytb) confirmed their maximum similarity with G1 genotype. Overall, high haplotype diversity (Hd) and a low nucleotide diversity (π) was identified based on diversity indices. For both the genes, non-significant negative values of Tajima’s D and Fu’s Fs indicate recent population expansion. Bayesian phylogeny-based results of nad5 and cytb sequences confirmed their genotypic status as distinct from other Echinococcus species. β-tubulins I, II and III were found as the candidate genes for deducing benzimidazole resistance.